110 A new insight into resolvin E3 as the itraconazole induced anticancer effect on cervical cancer. (13th November 2020) - Ueda, T; Tsubamoto, H; Shinohara, M; Takimoto, Y; Inoue, K; Isono, R; Sakata, K
Abstract : We have been studying drug repositioning of itraconazole for an anticancer drug. Previously, we reported clinical trials of patients with various types of cancer, and a window opportunity trial is ongoing (jRCTs051190006). Using uterine cancer cells, itraconazole inhibited cancer growth by downregulation of signal transduction (Akt/mTOR, hedgehog, Wnt/β-catenin). In this report, we investigated the bioactive lipid mediators (LMs) associated with itraconazole induced anti-cancer effect. Methods: CaSki cervical cancer cells before and after exposure to itraconazole were scraped and stored at -30 °C. LC-MS/MS–based metabololipidomics were performed. Deuterated internal standards representing each chromatographic region of identified lipid mediators were added to samples to facilitate quantification. The samples were extracted by automated SPE system on C18 columns and were then subjected to LC-MS/MS analysis with a Qtrap 6500 (Sciex) connected with a Shimadzu LC-30AD HPLC system. Biochemical pathway for LMs which increased more than 2 fold or decreased less than a half either at 30 min and 60 min after incubation with 10- 6 M itraconazole were subjected to the cell growth inhibitory experiments using WST assay. Results: Among downstream metabolites of eicosapentaenoic acid, resolvin E3 and resolvin E2 increased over 2 fold at 30 min and at 60 min, respectively. Coculture with 10M ML351, 12/15-LOX inhibitor responsible for the metabolism from 18-HEPE to resolvin E3, did not effect on the growth of CaSki cells. Coculture with 10M ML351 and 10- 6 M itraconazole attenuated the growth inhibitory effect of itraconazole (figure 1 ). Conclusion: Resolvin E3 could be a potential therapeutic target for the cancer treatment.